New Red-Flowered Crape Myrtles - Gary W. Knox (EDIS)
ENH-1019, a 4-page illustrated fact sheet by Gary W. Knox, describes the history of the development of red-flowered crape myrtles, planting and care, and characteristics and availability of various red-flowered cultivars. Published by the UF Department of Environmental Horticulture, May 2006.